The European Citizens’ Initiative “One of us”. A Gloss to the Judgment of the CJEU of 19 December 2019 in Case C-418/18 P. Puppinck and Others v. Commission - Parol, Agnieszka (Review of European and Comparative Law, 2024)
In December 2019, the Court of Justice issued a judgment in Case C-418/18 P. Puppinck and Others v. European Commission, ending a long-standing dispute between the organizers of the European Citizens’ Initiative “One of Us” and the EuropeanCommission. Ruling in the appeal proceedings, the CJEU dismissed in its entirety the application to set aside the judgment of the General Court of the European Union of 23 April 2018 in case T 561/14 One of Us and Others v. Commission. The “One of Us” organizing committee requested the repeal of the European Commission’s communication following the public initiative on the grounds that it lacked follow-up. The aim of the “One of Us” initiative was to strengthen the protection of dignity, the right to life and the integrity of every human being from conception in the EU’s areas of competence. The initiative proposed amendments to three legislative acts on research, humanitarian cooperation and their funding. The judgment under discussion is important for the interpretation of EU law in two areas. First, this is the first judgment that interprets the systemic position of the European Citizens’ Initiative in such a comprehensive manner. The case confirms that the ECI is an autonomous institution of EU law, whose systemic position is shaped by the principle of institutional balance and participatory democracy. The ECI is a form of emanation of deliberative democracy. Second, the judgment may be considered as confirming the exclusive competence of the Member States in the area of protecting human life at the prenatal stage. On the one hand, this means that EU law cannot impose its own standards on the right to life on Member States. On the other hand, in the area of its competences, it seems that the EU can have its own ethical position, allowing, while respecting the triple lock system, research involving the use of human embryonic stem cells and financing abortions as part of the package of medical assistance offered to the developing countries.